Guiding policies for agricultural nitrous oxide emission reduction with behavioral insights and experimentation - Tongzhe Li; Yong Liu; Alfons Weersink; Claudia Wagner-Riddle (npj Sustainable Agriculture)
Abstract Nitrogen fertilizer application causes emissions of nitrous oxide (N2O), a gas that contributes to global warming. N2O emission reduction is possible given technological advances. But climate policy for N2O reduction faces challenges caused by complex information, entangled risks with invisible gains, and polarized values. Behavioral factors influence farmers’ decision-making, and here we argue context-dependent experimentation is needed to develop N2O reduction policies, proposing crop insurance as an example policy.